1997
DOI: 10.1017/s003329179600431x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging and neuropsychological functions in dementia of the Alzheimer type

Abstract: These results underline the important role of the temporal substructures for aetiology and progression of DAT. They indicate that the volume of the AHC can be monitored by MRI and may be used to follow up the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 19 publications
(47 reference statements)
3
27
2
2
Order By: Relevance
“…Using quantitative MRI, Pantel et al (1997) compared the volumes of the temporal lobes, the frontal lobes, and the amygdala-hippocampus complex in 20 AD patients and 10 healthy control subjects. The AD patients were characterized by significant volume reductions in the temporal lobes and the amygdala-hippocampus complex, deficits that were already detectable in the mildly demented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using quantitative MRI, Pantel et al (1997) compared the volumes of the temporal lobes, the frontal lobes, and the amygdala-hippocampus complex in 20 AD patients and 10 healthy control subjects. The AD patients were characterized by significant volume reductions in the temporal lobes and the amygdala-hippocampus complex, deficits that were already detectable in the mildly demented.…”
Section: Discussionmentioning
confidence: 99%
“…Although memory problems are often subtle in the earliest stages of AD, their steady progression may leave the patient in an almost entirely amnestic condition. Recent neuroimaging studies have demonstrated structural (Jobst et al 1992;Pantel et al 1997), spectroscopic (Lazeyras et al 1998), and functional (Mann et al 1992;Pearlson et al 1992;Siegel et al 1995; for reviews, see Santens and Petit 1997;Small and Leiter 1998) cerebral changes in AD. These changes strike primarily the temporal and parietal association cortices but generally extend to the frontal cortex with progression of the disease (Buchsbaum et al 1991;Haxby et al 1988;Mann et al 1992;Mielke et al 1994;Smith et al 1992;Stein et al 1998), especially with secondary depression (Hirono et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive neuropsychological investigation was performed using a test battery which has been described in detail elsewhere [15]. Severity of cognitive impairment was established on the Mini Mental State Examination (MMSE) [21] and the Global Deterioration Scale (GDS) [22].…”
Section: Patients and Control Subjectsmentioning
confidence: 99%
“…Previous studies showed that MRI-based measurement of hippocampal size allows a separation of clinically diagnosed Alzheimer patients from age-matched nondemented controls with a sensitivity and specificity of 85-90% [9][10][11][12][13][14][15] and may also assist in the differential diagnosis of AD from age-associated memory impairment [16] and depressive pseudodementia [17]. However, the use of MRI-based volumetry in the differentiation of VD and AD remains to be established.…”
Section: Introductionmentioning
confidence: 99%